BAP1 Loss is a Useful Adjunct to Distinguish Malignant Mesothelioma Including the Adenomatoid-like Variant From Benign Adenomatoid Tumors - Erber, Ramona; Warth, Arne; Muley, Thomas; Hartmann, Arndt; Herpel, Esther; Agaimy, Abbas (Applied Immunohistochemistry & Molecular Morphology, 2020)
Malignant mesothelioma (MM) can show areas closely mimicking reactive mesothelial proliferations or recapitulating benign adenomatoid tumors (ATs) making distinction on occasion impossible on morphologic ground alone, particularly in limited biopsy material. Recently, loss of BAP1 by immunohistochemistry (IHC) has been suggested as a potential marker for identifying MM, but data is still limited. We studied 264 MM cases (257 using tissue microarrays; 7 on conventional slides) and 42 genital ATs for BAP1 immunohistochemical expression. Loss of BAP1 protein expression was observed in 119/211 of MM cases (56.4%). Taken by histologic type, 64.3% of biphasic, 55.4% of epithelioid, and 41.7% of sarcomatoid MM were BAP1-deficient. In contrast, all 42 ATs showed retained BAP1 immunoreactivity. Notably, all 4 MM cases with variable adenomatoid-like features were BAP1-deficient. Surface components of MM of the pleura showed concordant loss as the invasive tumor suggesting a potential role for BAP1 loss for recognizing so-called early mesothelioma. In conclusion, BAP1 loss demonstrated by IHC is seen in more than half of MM cases but none of ATs. Thus, BAP1 IHC represents a potential adjunct for distinguishing MM from benign mesothelial proliferations including in particular "MM with bland adenomatoid-like pattern versus benign ATs" on biopsy material and early mesothelioma with limited invasion.
CRIS-Team WoS Importer:2020-01-07